Sustainable Plans and Mutual Default - Chari, V. (IMF Working Papers; Working Paper ;, 1990)
This paper presents a model of optimal taxation in which both private agents and the government can default on their debt. We first consider Ramsey equilibria in which the government can precommit to its policies but in which private agents can default. We then consider sustainable equilibria in which both government and private agent decision rules are required to be sequentially rational. We show that when there is sufficiently little discounting and government consumption fluctuates enough, the Ramsey allocations and policies (in which the government never defaults) can be supported by a sustainable equilibrium.